POLA PERILAKU PENGHUNI DI DALAM HUNIAN SAAT PANDEMI COVID-19 - Hana Hali Nurrahmada; Hanson E. Kusuma; Allis Nurdini (EMARA: Indonesian Journal of Architecture, 2022)
During the COVID-19 pandemic, housing is not only a protector and a shelter; it also accommodates all activities, both working and studying. The changes that have occurred as a result of the stay-at-home policy have made residents make various changes to their activities and adjustments to their homes. This study aims to reveal the correlational relationship between perceptions of satisfaction, changes in activities, and housing adjustments during the COVID-19 pandemic. so that it can be determined what the pattern of behaviour in the house was during the COVID-19 pandemic. This study uses qualitative methods in the first stage and quantitative methods in the second stage. The first stage investigates all changes in activity and adjustments made in the house during the pandemic. The second stage reveals the relationship between activities, mental adjustment, and perceived satisfaction in housing, including productive groups, family-oriented groups, and self-oriented groups. Productive groups tend to correlate with forms of adaptation in the form of cleaning activities, semi-public activities, and adjustments through the configuration of space and functions. Then, closeness to a family group tends to correlate with diversification activities such as online activities, online shopping, cleaning activities, room cleanliness, and increased space privacy. Meanwhile, self-oriented groups tend to correlate with activities in the room, recreational activities, and privacy enhancements. The behavioural patterns of occupants in housing during the COVID-19 pandemic that were found in this study can contribute to future residential design considerations.